Molecular analysis of ammonia oxidation and denitrification in natural environments - Bothe, Hermann; Jost, Günter; Schloter, Michael; Ward, Bess B; Witzel, Karl-Paul (FEMS microbiology reviews, 2000)
This review summarizes aspects of the current knowledge about the ecology of ammonia-oxidizing and denitrifying bacteria. The development of molecular techniques has contributed enormously to the rapid recent progress in the field. Different techniques for doing so are discussed. The characterization of ammonia-oxidizing and -denitrifying bacteria by sequencing the genes encoding 16S rRNA and functional proteins opened the possibility of constructing specific probes. It is now possible to monitor the occurrence of a particular species of these bacteria in any habitat and to get an estimate of the relative abundance of different types, even if they are not culturable as yet. These data indicate that the composition of nitrifying and denitrifying communities is complex and apparently subject to large fluctuations, both in time and in space. More attempts are needed to enrich and isolate those bacteria which dominate the processes, and to characterize them by a combination of physiological, biochemical and molecular techniques. While PCR and probing with nucleotides or antibodies are primarily used to study the structure of nitrifying and denitrifying communities, studies of their function in natural habitats, which require quantification at the transcriptional level, are currently not possible.